Transformational leadership and its influence on pupils' academic achievement in primary schools in Tanzania - Vicent Boniface Kayombo; Rose Ephraim Matete; Majiyd Hamis Suru (Освітній вимір, 2025)
In this study, we explored the influence of transformational leadership style on pupils' academic performance in primary schools in Tanzania. A mixed-methods research approach and convergent parallel design were employed. The study involved 382 participants, i.e., 356 primary school teachers and 14 headteachers, and 12 Ward Education Officers (WEOs). Data was collected through questionnaires and interviews, and analysed through descriptive and regression models for quantitative, and thematically for qualitative. The results indicate a strong correlation between transformational leadership practices and the academic achievement of pupils in primary schools. The results suggest that individualised consideration and intellectual stimulation significantly contributed to positive pupils' achievement. The results again showed a notable association between personalised approaches and satisfactory academic performance. In addition, the results indicate that an environment characterised by intellectual stimulation increases the likelihood of achieving satisfactory performance. The results, however, indicate no direct relationship between inspirational motivation and pupils' academic achievement. The key argument in this study is that school leaders need to use a transformational leadership style to motivate teachers to work hard for effective pupil learning. For this to occur in reality, school leaders and their teachers need training to create an engaging and supportive learning environment conducive to improving pupils' achievement.